The ‘Smart Region’ Concept: The Implementation of Digital Technology - LYSHCHIKOVA, Julia V.; STRYABKOVA, Elena A.; GLOTOVA, Anastasia S.; DOBRODOMOVA, Tatiana N. (Journal of Advanced Research in Law and Economics, 2019)
The article is devoted to the identification and systematization of theoretical and methodological approaches to the formation of the concept ‘smart region’ in Russia and abroad. The objects of the research are the processes of the sustainable spatial development of a region as a geographically-localized ecosystem of the digital economy. The subject of the research is the organizational, economic and managerial relations that arise in the process of formation and institutionalization of the concept ‘smart region’ in the management of sustainable spatial development. The authors have found that the concept ‘smart region’ is an evolutionary idea. Its main content is the creation and development of the region as competitive in the national and global aspects economic system and safe and comfortable for a person socio-territorial community, determined by a set of economic, social and environmental factors based on the implementation of modern information and communications and other technologies.